2013
DOI: 10.1186/2193-1801-2-65
|View full text |Cite
|
Sign up to set email alerts
|

Technical efficiency in milk production in underdeveloped production environment of India*

Abstract: The study was undertaken in Kumaon division of Uttarakhand state of India with the objective of estimating technical efficiency in milk production across different herd-size category households and factors influencing it. Total of 60 farm households having representation from different herd-size categories drawn from six randomly selected villages of plain and hilly regions of the division constituted the ultimate sampling units of the study. Stochastic frontier production function analysis was used to estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 5 publications
2
8
0
Order By: Relevance
“…Holding a contrary view, [29] noted that owners of small scale farms tend to work on their farms and appropriate the full benefits of their efforts unlike large scale farmers who use hired labor which is rarely found to be least concerned with farm progress. Results of Herd size effect on efficiency for [30] was positive and statistically significant while [31] observed a significant and negative relationship between herd size and technical efficiency in milk production in underdeveloped production environment of India. Herd size was expected to affect technical efficiency in either direction.…”
Section: Factors That Influence Technical Efficiencymentioning
confidence: 83%
“…Holding a contrary view, [29] noted that owners of small scale farms tend to work on their farms and appropriate the full benefits of their efforts unlike large scale farmers who use hired labor which is rarely found to be least concerned with farm progress. Results of Herd size effect on efficiency for [30] was positive and statistically significant while [31] observed a significant and negative relationship between herd size and technical efficiency in milk production in underdeveloped production environment of India. Herd size was expected to affect technical efficiency in either direction.…”
Section: Factors That Influence Technical Efficiencymentioning
confidence: 83%
“…The cow is considered holy in Indian mythology, and the anti‐viral and anti‐bacterial properties of cow urine and dung has long been established (Samhita, ; Basak et al., ; Jarald et al., ). India is the leading milk producer in the world (More, ), but this achievement is number driven (Birthal et al., ), and native breeds of Indian livestock are known for their low per‐animal productivity (Bardhan and Sharma, ).…”
Section: Discussionmentioning
confidence: 99%
“…This section presents the determinants of TE and the formulation of hypotheses derived from the literature. Several authors have discussed the determinants of TE, since understanding these factors can improve the efficiency and performance of dairy farms (Tauer and Belbase, 1987;Bravo-Ureta and Rieger, 1991;Hallam and Machado, 1996;Gelan and Muriithi, 2012;Ma et al, 2012;Nascimento et al, 2012;Bardhan and Sharma, 2013;Luik et al, 2014;Van der Voort et al, 2014;Gül et al, 2016;Travassos et al, 2016;Latruffe et al, 2017;Mehmood et al, 2018). Mareth et al (2017) identified 42 studies that analyse the determinants of TE in dairy farms.…”
Section: Methodsmentioning
confidence: 99%